2013
DOI: 10.3390/jcm2040242
|View full text |Cite
|
Sign up to set email alerts
|

How do Midwives and Physicians Discuss Childhood Vaccination with Parents?

Abstract: Even if vaccination is often described as one of the great achievements of public health, results of recent studies have shown that parental acceptance of vaccination is eroding. Health providers’ knowledge and attitudes about vaccines are important determinants of their own vaccine uptake, their intention to recommend vaccines to patients and the vaccine uptake of their patients. The purpose of this article is to compare how midwives and physicians address vaccination with parents during pregnancy and in post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 41 publications
3
30
0
Order By: Relevance
“…One study highlighted the importance of using DAs in a flexible manner, that is, adapted to timing appropriate to the needs of different types of health professionals [ 40 ]. The variation in intention could also be explained by their different views regarding their role and responsibilities [ 46 - 48 ]. For instance, although midwives see their role more as one of “providing information” and letting the patient decide, physicians more often consider their role as that of an “advisor” or an “educator” and feel the decision is their responsibility [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study highlighted the importance of using DAs in a flexible manner, that is, adapted to timing appropriate to the needs of different types of health professionals [ 40 ]. The variation in intention could also be explained by their different views regarding their role and responsibilities [ 46 - 48 ]. For instance, although midwives see their role more as one of “providing information” and letting the patient decide, physicians more often consider their role as that of an “advisor” or an “educator” and feel the decision is their responsibility [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, less than half of midwives in Ontario reported having sufficient knowledge of immunisation (Lee, Saskin et al 2005). A recent survey of health providers in Belgium found one-quarter of midwives recommended influenza and pertussis vaccines to their pregnant patients (Maertens, Braeckman et al 2016), and a similar study from Canada suggested midwives take a less active role in promoting immunisation compared to other healthcare providers (Dube, Vivion et al 2013). This study aimed to assess the knowledge, attitudes and learning needs of midwives in hospital X, the only public tertiary maternity hospital in the Australian state of XX.…”
Section: Introductionmentioning
confidence: 99%
“…In a qualitative study pertinent to the health promotional aspect of midwifery immunisation education, Dube et al 10 compared the attitudes and practices of midwives and physicians in Quebec. The latter were comfortable taking a didactic approach, telling parents to vaccinate, whereas the midwives specified that their job was to inform, not instruct.…”
mentioning
confidence: 99%
“…Midwifery ideology and professional practice privilege maternal autonomy and agency as sacrosanct with regard to pregnancy and birth choices well beyond vaccination. 10 Student midwives learn about vaccination within this cultural context. Hence, we need to consider the depth of vaccination education as part of midwifery degrees, including the amount of time dedicated, the immunisation experience of the lecturer, how maternal autonomy is presented, and whether counselling in favour of vaccination is countenanced.…”
mentioning
confidence: 99%